Associations Among Depressive Symptoms, Childhood Abuse, Neuroticism, Social Support, and Coping Style in the Population Covering General Adults, Depressed Patients, Bipolar Disorder Patients, and High Risk Population for Depression - Zhou, Jia; Feng, Lei; Hu, Changqing; Pao, Christine; Xiao, Le; Wang, Gang (Frontiers in Psychology, 2019)
Abstract Background: Exposure to childhood abuse has been identified as a salient risk factor for the development of depression. However, the mediating factors between childhood abuse and depressive symptoms have not been sufficiently elucidated. This study aims to investigate the mediating effects of neuroticism, social support, and coping style between childhood abuse and depressive symptoms in population covering general adults, depressed patients, bipolar disorder patients, and high risk population for depression. Methods: This is a cross-sectional study. Five validated questionnaires were used to measure the psychological outcomes (Childhood Trauma Questionnaire CTQ-SF, Eysenck Personality Questionnaire EPQR-S, Simplified Coping Style Questionnaire SCSQ, and Patient Health Questionnaire-9 PHQ-9) of 312 participants. Multiple regressions and structural equation modeling were used to conduct data analysis. Results: Multiple regression analysis and structural equation modeling showed a significant association between childhood emotional abuse and depression symptoms. Neuroticism, use of social support, and active coping style were important mediating variables of this association. The R2 for our model was 0.456, indicating that 45.6% of the variability in depressive symptoms can be explained by the model. Conclusions: This study suggested that neuroticism, active coping and use of social support paly important role in mediating the effects of childhood abuse on adult depressive symptoms.